2021
DOI: 10.1038/s41598-021-83019-0
|View full text |Cite
|
Sign up to set email alerts
|

Rapid seroconversion and persistent functional IgG antibodies in severe COVID-19 patients correlates with an IL-12p70 and IL-33 signature

Abstract: Despite ongoing efforts to characterize the host response toward SARS-CoV-2, a major gap in our knowledge still exists regarding the magnitude and duration of the humoral response. Analysis of the antibody response in mild versus moderate/severe patients, using our new developed quantitative electrochemiluminescent assay for detecting IgM/IgA/IgG antibodies toward SARS-CoV-2 antigens, revealed a rapid onset of IgG/IgA antibodies, specifically in moderate/severe patients. IgM antibodies against the viral recept… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 33 publications
2
27
0
1
Order By: Relevance
“…Consistent with the strong epithelial damage observed in SARS-CoV2 lungs, global transcriptomic analyses of cells within the bronchoalveolar fluid indicated that the expression of IL-33 is upregulated in lungs of patients suffering from COVID-19 disease ( 66 ). In line with this, IL-33 blood concentrations were reported to be increased during active disease ( 67 , 68 ). Moreover, the expression of IL-33 after stimulation of COVID-19 convalescent peripheral blood mononuclear cells with SARS-CoV2 peptides correlated with seropositivity for the viral spike glycoprotein ( 69 ) indicating that ILC2s or other ST2 + cells such as T cells, B cells and macrophages are functionally linked to the disease.…”
Section: Ilc2s As Gatekeepers Of Lung Homeostasissupporting
confidence: 63%
“…Consistent with the strong epithelial damage observed in SARS-CoV2 lungs, global transcriptomic analyses of cells within the bronchoalveolar fluid indicated that the expression of IL-33 is upregulated in lungs of patients suffering from COVID-19 disease ( 66 ). In line with this, IL-33 blood concentrations were reported to be increased during active disease ( 67 , 68 ). Moreover, the expression of IL-33 after stimulation of COVID-19 convalescent peripheral blood mononuclear cells with SARS-CoV2 peptides correlated with seropositivity for the viral spike glycoprotein ( 69 ) indicating that ILC2s or other ST2 + cells such as T cells, B cells and macrophages are functionally linked to the disease.…”
Section: Ilc2s As Gatekeepers Of Lung Homeostasissupporting
confidence: 63%
“…Regarding to the relationship between antibodies and cytokines, anti-spike 1 IgG antibodies presented a positive correlation with EGF and IL-8 and an inverse correlation with IP-10, IFN-g and G-CSF. A previous study only found a correlation with IL-12p70/IL33 and IgG seroconversion, which correlated with disease severity (39). However, another study hypothesized that IL-8 and overall, the inflammation acts as a mediator between the association of IgG antibodies and the clinical outcome (40).…”
Section: Discussionmentioning
confidence: 96%
“…This observation is interesting in the context of the current SARS-CoV-2 epidemic, which has revealed the importance of the “cytokine storm” in severe forms of infection [ 34 ]. These gravely affected patients are likely to produce alarmins, such as IL-33, as well as IL-12 [ 35 , 36 ]. It has been reported that the number of MAIT cells, which account for up to 10% of circulating CD3+ T cells, decreased significantly in peripheral blood from COVID-19 patients, while their activation was associated with poor clinical outcome [ 37 ].…”
Section: Discussionmentioning
confidence: 99%